The use of organic calcium derived from eggshell waste on physiological and intestinal conditions of broiler chickens - Sugiharto, S.; Tentrawinata, Z. I.; Wahyuni, H. I.; Widiastuti, E.; Yudiarti, T.; Agusetyaningsih, I.; Raza, M. A. (Diponegoro University, 2024)
The study aimed to investigate the effect of using eggshell waste or eggshell extract as organic calcium source in feed on the physiological conditions and intestines of broilers. A total of 392 one-day-old chicks were randomly distributed into four groups (10 birds each group), CONT (control diet con taining 1% limestone as an inorganic calcium source), EGFL (feed containing 1% eggshell powder as an organic calcium source), EEG1 (feed containing 1% eggshell extracted with Averrhoa bilimbi L. fruit filtrate as an organic calcium source), and EEG05 (feed containing 0.5% eggshell extracted using A. bilimbi L. fruit filtrate). Body weight and feed intake were recorded weekly, whereas blood, intesti nal content, and small intestinal segments were collected at day 35. Our results showed that during days 8-35, weight gain and feed consumption were lower (P<0.05) in EEG05 than in CONT and EGFL. Thymus relative weight tended (P=0.08) to be lower in EEG05 than in CONT, and gizzard was lower (P<0.05) in EGFL than in CONT and EEG05. Serum total triglyceride was significantly higher in CONT than in other groups. Moreover, serum high-density lipoprotein was higher in EEG1 and EE G05 than in CONT (P<0.05). furthermore, serum albumin were higher (P<0.05) in EEG1 than in CONT, EGFL and EEG05. Additionally, serum uric acid was higher (P<0.05) in EEG1 than in EGFL and EEG05. Among the groups, SGPT levels were lowest (P<0.05) in EEG05 birds. While there was no effect (P>0.05) of treatments on coliform and lactic acid bacteria in the ileum and caecum, jejunal crypt depth tended (P=0.09) to be lower in EEG1 and EEG05 than in CONT and EGFL broilers. Con clusively, using 1% eggshell powder or eggshell extract in feed as the substitute for limestone had no detrimental effect on broiler chickens’ growth, physiological status and intestinal condition. Hence, eggshell powder or eggshell extracted with A. bilimbi L. fruit filtrate can be used as an organic calcium source to replace limestone.